Synergistic effect of polymorphism, substrate conductivity and electric field stimulation towards enhancing muscle cell growth in vitro. Issue 13 (26th January 2016) - K, Ravikumar; Kar, Goutam Prasanna; Bose, Suryasarathi; Basu, Bikramjit
Abstract : Poly(vinylidene difluoride), a well-known candidate for artificial muscle patch applications is a semi-crystalline polymer with a host of attributes such as piezo- and pyroelectricity, polymorphism along with low dielectric constant and stiffness. Abstract : Poly(vinylidene difluoride), a well-known candidate for artificial muscle patch applications is a semi-crystalline polymer with a host of attributes such as piezo- and pyroelectricity, polymorphism along with low dielectric constant and stiffness. The present work explores the unique interplay among the factors (conductivity, polymorphism and electrical stimulation) towards cell proliferation on poly(vinylidene difluoride) (PVDF)-based composites. In this regard, multi-walled carbon nanotubes (MWNTs) are introduced in the PVDF matrix (limited to 2%) through melt mixing to increase the conductivity of PVDF. The addition of MWNTs also led to an increase in the fraction of piezoelectric β-phase, tensile strength and modulus. The melting and crystallization behaviour of PVDF–MWNT together with FT-IR confirms that the crystallization is found to be aided by the presence of MWNT. The conducting PVDF–MWNTs are used as substrates for the growth of C2C12 mouse myoblast cells and electrical stimulation with a range of field strengths (0–2 V cm −1 ) is intermittently delivered to the cells in culture. The cell viability results suggest that metabolically active cell numbers can statistically increase with electric stimulation up to 1 V cm −1, only on the PVDF + 2% MWNT. Summarising, the current study highlights the importance of biophysical cues on cellular function at the cell–substrate interface. This study further opens up new avenues in designing conducting substrates, that can be utilized for enhancing cell viability and proliferation and also reconfirms the lack of toxicity of MWNTs, when added in a tailored manner.